EKPRESI WAJAH ANAK-ANAK DALAM KARYA LUKIS EKSPRESIONIS - SYAFI’I FABLI, Drs. Idran Wakidi, M.Pd., Drs. Abd. Hafiz, M.Pd (Universitas Negeri Padang, 2019)
The creation of this final work aims to visualize children's facial expressions as a concept for the creation of paintings. Displays ten children's facialexpressions above a two-dimensional field.The method and process of work used in the creation of this painting work goes through several stages: 1 preparation, 2 Elaboration, 3 Synthesis, 4 Realization of the Concept, 5 Completion.The results of the visualization of children's facial expressions in this painting are 10 works with the titles: 1 Tense, 2 Comfortable, 3 Fear, 4 Spontaneous, 5 Sad, 6 Embarrassed, 7 Sullen, 8 Happy, 9 Emotions, 10 Happy.Keywords: Facial expressions, children, painting, expressionism